Capillary electrophoresis-based detection of cow milk adulteration in specialty milks and products: Physicochemical characteristics of potential markers - Shuobo Jia; Xiaoyue Wang; Chunxia Deng; Bohao Zhang; Rongwei Han; Qijing Du; Hongning Jiang; Tongjun Guo; Dengpan Bu; Yongxin Yang (Journal of Dairy Science)
ABSTRACT: Specialty milks, known for their distinct nutritional profiles and expensive pricing, have received increased attention as a result of worries over their adulteration with cow milk. This study used capillary electrophoresis to detect cow milk adulteration (2%, 5%, 10%, 30%, and 50%) in raw, pasteurized, freeze-dried, and spray-dried forms of 7 specialty milks (buffalo, yak, goat, sheep, camel, horse, and donkey) and to identify particular markers derived from cow components. Cow αS1-CN, β-CN A1, β-LG, and α-LA were identified as potential markers for detecting cow milk adulteration in specific milk types, based on their retention times. Among these, αS1-CN was capable of detecting 2% cow milk adulteration in raw sheep, camel, and horse milks, and 5% adulteration in raw buffalo, goat, and donkey milks. β-LG, on the other hand, detected 5% cow milk adulteration in raw goat and camel milks, and 30% adulteration in raw horse and donkey milks. The detection limit for αS1-CN, and β-LG in freeze-dried milk powder remained unaltered compared with raw milk. However, the detection limit increased in pasteurized and spray-dried forms, which was connected with particular milk markers. αS1-CN and β-LG from cow and specific milk were characterized following separation, revealing significant differences in particle size and surface hydrophobicity between cows and specific species. These variations contributed to differences in the retention times observed during capillary electrophoresis analysis. This study laid the groundwork for using capillary electrophoresis to detect adulteration in specialized milks and their processed products, providing useful insights into the physicochemical features of potential markers.